KONSUMSI SUKUN MEMBANTU PENYERAPAN TABLET FE DALAM PERUBAHAN KADAR HEMOGLOBIN IBU HAMIL - Nurhidayati Nurhidayati; Puji Hastuti; Tuti Sukini; Arfiana Arfiana (Jurnal Sains Kebidanan, 2020)
Iron absorption is influenced by the availability of vitamin C to help reduce ferric iron (Fe3 +) to ferrous (Fe2 +) in the small intestine so that it is easily absorbed. Breadfruit is an alternative food consumption to increase iron absorption because it contains vitamin C fruit around 29-62 mg per 100 grams. Pregnant women are prone to iron deficiency anemia due to hemodilution, lack of iron in food and increased need for iron as well as digestive disorders and absorption. Anemia incidence of pregnant women in Cilacap Regency in 2018 was 37.30% and in Kroya District was 31.61%.. The purpose of this study was to determine the effect of consumption of breadfruit to help the absorption of Fe tablets on changes in hemoglobin levels in pregnant women.Type of research Quasy experiment with a Non-rondomized Control Group Pretest - Postest Design research design The research instrument used a questionnaire and a Photometer 4010 Boehringer Mannheim accuracy of 0.01 g / dL.The results showed influence of breadfruit consumption to help the absorption of tablets Fe on changes in hemoglobin levels in pregnant women (probability value 0.001).